Faktor – Faktor Penyebab Berkembangnya Terorisme di Indonesia Kurun Waktu 2002 – 2005 - Mulyawan, Brian Adam (Global and Policy Journal of International Relations, 2014)
ABSTRACTJama’ah Islamiyah (JI) is international terrorism was build in 1993 by Abdullah Sungkar andtargeting Indonesia as his preaching area. Since there was conflict in JI international causedthree thoughts. Ideologist faction led by Abu Rushdan, moderate faction led by Abu BakarBa’asyir, extreme radical faction led by Hambali and Zulkarnaen. Jama’ah IslamiyahIndonesia Mantiqi Tsani II, Mantiqi Ula I which led by Hambali and Noordin M. Top jihadused bomb exploded in Bali. That tragedy happened because there was terrorism enteredIndonesia’s weak borders and the use of internet as a tool to share information for spreadingterrorism in Indonesia. This article uses descriptive analysis method which included inqualitative research. Qualitative method is based on Miles and Huberman (1992) theory,which has 3 qualitative data analysis. First, data reduction; second, data serving; and third,conclusion. Concepts in this article are National Security, Territorial Border, and Network.Result of this research is based on literature analysis which can help writer finds connectedvalid data and gives conclusion to know the causes of spreading terrorism in Indonesia.Keywords: Territorial Border, Terrorism, NetworkDOI:https://doi.org/10.33005/jgp.v2i02.2066